Motivasi Wisatawan Berkunjung ke Agrowisata Batu Patah Payo kota Solok - Anggika Sigit; Hijriyantomi Suyuthie (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2022)
This research was initially motivated by a problem where motivation is what makes tourists carry out tourism activities to see how the motivation of tourists to visit Payo agro-tourism in Solok City, with quantitative descriptive research and survey methods. The tourists who are the samples in this study are people who have visited and are currently visiting Payo Agrotourism, Solok City and the technique of determining the sample is accidental sampling. Data collection techniques by distributing questionnaires with 13 statements related to tourist motivation. Based on the results of the study, it was found that the motivation value of tourists visiting Payo Agrotourism in Solok City was found in the very good category with a percentage of 71%, which means that the motivation of tourists visiting Payo Agrotourism in Solok was in the very good category. The indicators of physical motivation are categorized as very good and the percentage is 50%. indicators of interpersonal motivation are in the very good category with a percentage of 72%. indicators of motivation status and dignity are categorized as very good at the percentage of 94%%. indicators of cultural motivation are classified in the bad category with a percentage of 47%.